The role of implementing carbon market scheme and carbon trading as an effort to mitigate climate change - Nasir, Aqiqah Amalia (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Increasing the amount of greenhouse emissions is a challenge that must be faced considering that these emissions are one of the causes of greenhouse gases, the implementation of carbon markets and carbon trading is an effective effort to implement. Background: This journal aims to examine the role of carbon trading and carbon markets in reducing global emissions. Methods: The data collection method uses a literature review of reading materials that are relevant to the topic and uses qualitative analysis techniques. Finding: From the results of the research it can be seen that the application of an emission trading system is the right thing to implement to reduce carbon emissions, but in its implementation it still requires cooperation from several parties. Conclusion: The concept of trade and carbon market is very urgent to be implemented in Indonesia considering the deteriorating environmental conditions that will affect the quality of public health. The implementation of this system can achieve the emission reduction target as committed by Indonesia at the international level.